THE INTERRELATIONSHIPS BETWEEN NATURE AND CULTURE IN ENGLISH AND KARAKALPAK PROVERBS - Kurbanbaev Djavod Aminbaevich (Western European Studies, 2025)
This narrative study examines how embodied cognition and linguoculturology work together in the meaning of English and Karakalpak proverbs. I read attested proverb pairs (Latin script for Karakalpak) through conceptual metaphor mappings and value-oriented cultural commentary. The analysis focuses on recurring images – forge/heat, orchard/gravity, precious metals, and local fauna – and groups the data as full, partial, and functional nonequivalents. Results show that shared cognitive frames (opportunity as heat, resemblance as proximity, prudence and restraint) are realized through culture-specific imagery that reflects craft traditions, rural ecology, and social etiquette. Differences in numeric heuristics and rhythmic form also support memory and norm strength in distinct ways. I argue that proverb analysis is an effective laboratory for observing the co-evolution of thought and culture, and I outline practical implications for pedagogy (concept-first explanations, equivalence matrices) and for future corpus building with standardized orthography.
Keywords: cognitivism; linguoculturology; embodied cognition